THE DEVELOPMENT OF TRADITIONAL GAME MODEL BAKUBAKU RAJA FOR BASIC MOTION FOR STUDENTS BASIC GRADE ELEMENTARY SCHOOL IN PALU CITY - Hendriana Sri Rejeki (Universitas Muhammadiyah Semarang, 2018)
The purpose of this research is to develop the learning model of Traditional Game of King Raws for the basic motion of catching the students of lower grade elementary school in Palu city.Characteristicsof the model developed is a model of throwing and catching learning for students in Primary School with tools such as bracelets, walking rods, ribbons, whistles, and lime. This research was conducted in PaluCentral Sulawesi, namely: SDN Tanah Modindi, SDN Kawatuna, and SDN 1 Paboya. Research and development in this learning using qualitative approach and using Research & Development (R & D) research method consisting of ten steps from Borg and Gall. Based on the data obtained, from the results of small group trials and field trials and discussion of research results, it can be concluded that the traditional game model Baku - Baku King for basic motion capture for elementary school students lower classes can be developed in learning throwing catch for lower school students basic. Keywords: Development, Traditional Game Model, Throwing Capture